Evaluating 15-minute walkable life circles for the senior: a case study of Jiande, China - Zhen Xu; Ziqi Shang; Yufu Zhong; Lingyun Han; Mingyu Li; Yihan Yang (Journal of Asian Architecture and Building Engineering, 2025)
Walking is the primary travel mode for daily errands, leisure, and accessing local services, particularly for most seniors. Sufficient and diverse facilities within walking distance help improve seniors’ well-being. Countries today face the challenge of providing enough facilities for more seniors and adopt some possible solutions, such as China’s 15-minute community life circle. Focused on Jiande, a medium-sized city in southeast China, we propose an assessment framework with three dimensions: availability, diversity, and balance among medical, living, and leisure facilities. Using GIS network analysis, this study reveals disparities in facility provision at the household-level between earlier and newer developed urban areas, which are closely related to geographical factors and gated communities. This is common in Chinese cities, suggesting the cumulative effects of urban development sequences. To alleviate and prevent serious service inequity, we propose the following two strategies to achieve an equally walkable city: increasing landscape services to overcome geographical obstacles and implementing open-gated community strategies. Furthermore, the limitations of relying solely on big data to calculate walking routes were noted. This diagnostic framework for assessing city environments for seniors is straightforward yet comprehensive and potentially promotes cooperation between planning professionals, policymakers, and the public.